Preparation of a Veterinary Supplement That Reduces Aflatoxin B1 Availability - Mălina Deșliu-Avram; Carmen Lupu; Simona Rotaru; Diana Constantinescu-Aruxandei; Radian Nicolae Negrilă; Florin Oancea (Chemistry Proceedings)
This work describes the preparation of a veterinary supplement based on diatomaceous earth, chemically hydrolyzed proteins, and essential oils, which are applicable for protecting monogastric animals against the mycotoxin contamination of cereal-based feeds. The veterinary supplement comprises 54.5–55% diatomaceous earth, 40.5–41% hydrolyzed proteins (whey protein concentrate and soybean protein isolate), 2.4–2.5% oregano essential oils, 0.6–0.7% NaCl, and 1.6% CaCl2. The preparation process includes alkaline thermal hydrolysis of proteins, followed by emulsification of the essential oil with protein hydrolysate and granulation with diatomaceous earth. The veterinary supplement prepared in this work reduces the availability of aflatoxin B1 in a simulated gastric fluid by 82.7 ± 4.43%.